The Influence Of Work Life Balance In Islamic Perspective And Job Satisfaction On Turn Over Intention Of Employee At The University Of Darussalam Gontor Female Campus - Suyanto; Elsa Andriyani; Hasni, Gina Atikah (University of Darussalam Gontor, 2024)
Turn Over Intention in an organization is very important because to see the success of a manager in leading a company, the creation of Work Life Balance in Islamic Perspective and Job Satisfaction within the scope must receive special attention All of this will have a positive impact on employee performance. This research aims to analyze and find out whether Work Life Balance in an Islamic Perspective and Job Satisfaction influence Turnover Intention of employees at the University of Darussalam Gontor Female Campus The research method used was descriptive quantitative with a population of 106 Darussalam Gontor University employees, using a non-probability sampling type, namely a saturated sample. The results show that Work Life Balance in Islamic Perspective has no effect on Turn Over Intention, Job Satisfaction has a negative effect on Turn Over Intention, Work Life Balance in Islamic Perspective and Job Satisfaction have an effect on Turn Over Intention.